What was your dream, Dr. King? : and other questions about Martin Luther King, Jr. - Carson, Mary Kay (Sterling Children's Books, 2013)
An introduction to the example and achievements of the influential civil rights leader poses and answers key questions about his life and time, offering insight into such topics as segregation, the 1963 Civil Rights March, and the history and purpose of his famous speeches.